O princípio da soberania popular e a questão das minorias: a legitimidade das decisões contramajoritárias à luz da filosofia política do reconhecimento. - Bringel, Elder Paes Barreto (2015)
This master s thesis focuses on a discussion that was raised in the constitutional debate of contemporaneity, having as the main point, the conflict between the democratic principle of popular sovereignty and the constitutional jurisdiction when it takes a different turn from the one indicated by the representatives, elected by the people, for the exercise of the creative function of law. Therefore, we seek to establish, in the first line of reasoning, the latest source of the democratic form of government, ending with the trichotomic structuring of the institute, based on popular sovereignty, and constitutionality review and human rights. Assuming that democratic states of the contemporary law are supported in these three pillars (popular sovereignty, constitutionality review and human rights), we point to the urgent need for envisioning a democratic exercise that goes beyond a purely quantitative criteria, including necessarily the interests of minorities on the agenda for debates and public policy choices. In this bias, the present study relocates the issue of minorities to the center of the debate discussing the apparent conflict between democracy and constitutional jurisdiction, raising the hypothesis that there is a compatibility between institutes from the moment you envision minorities as part of the operative gear. We defend throughout this writing that the constitutionality review exercised by constitutional courts, although they follow a different path chosen by the legislator derivative - and be therefore classified as majority against - is legitimate where decisions have been made under the auspices of recognizing fundamental rights to democratically underrepresented minorities. At last, we conclude with the legitimacy of majority against decisions taken by the Supreme Court in defense of minority rights, sustained this possibility under the theoretical pillars of the political philosophy of recognition-redistribution, the more closely inspired by the writings of Axel Honneth and Nancy Fraser, and the democratic constitutionalism defended by Robert Post and RevaSiegel.